The clinical learning environment, supervision and nurse teacher scale (CLES+T): psychometric properties measured in the context of postgraduate nursing education - Dorota Ozga; Aleksandra Gutysz-Wojnicka; Bogumił Lewandowski; Beata Dobrowolska (BMC, 2020)
Abstract Background The Clinical Learning Environment, Supervision and Nurse Teacher Scale (CLES+T) instrument is internationally used for the evaluation of clinical learning environment in undergraduate nursing education. However, no evidence is available on the possible applications of this instrument in the context of postgraduate nursing education. Purpose To examine the basic psychometric properties of CLES+T in the context of clinical postgraduate nursing education in Poland. Methods Study among a sample of 417 nurses participating in the clinical postgraduate training in Poland. Results Cronbach's alpha for the total scale was 0.97. A five-factor structure was confirmed in accordance with the assumptions adopted by the authors of the original version of the scale. Cronbach's alpha coefficient for the Polish version of the CLES+T subscales ranged from 0.83 (Nursing care on the ward) to 0.95 (The content of supervisory relationship). The mean results for individual subscales ranged from 4.52 ± 0.63 for nursing care on the ward to 4.73 ± 0.45 for role of the nurse teacher. Conclusions Having shown satisfactory psychometric properties, CLES+T can be considered a useful instrument to assess those elements of clinical learning environment which are important for the assurance of education quality at the postgraduate level.